Penerapan Model PjBL ditinjau dari Kurikulum Merdeka dalam Mengembangkan Kreativitas Belajar Ekonomi SMAN 12 Medan - Nur Adawiyah Harahap; Vailimlim Simamora; Della Aulia Br. Ginting; Lusyana Karolina Sidebang; Andi Taufiq Umar (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This type of research is a qualitative research type case study that aims to examine the application of the Project-based Learning (PjBL) model in the Independent Curriculum and its impact on the development of economic learning creativity of grade XI students at SMAN 12 Medan. One of the learning strategies in the independent curriculum that has flexibility and is student-centered is project-based learning (PjBL) which can increase student involvement and creativity in learning. The respondents who became the subject of this study were 10 students of class XI. Based on the results of interviews and observations, it was found that PjBL had a positive influence on student learning creativity. The PjBL elements implemented at school, namely project activities to strengthen the profile of Pancasila students (P5) and the School Creative Bazaar, are able to motivate students to think creatively and improve entrepreneurial skills. Although, students face many challenges in adapting to this learning. Other results also show that the PjBL strategy in Merdeka Curriculum is effective for developing students' creativity and learning motivation, with significant differences compared to other curricula such as K13 and KTSP. This study concludes that PjBL in the Merdeka Curriculum can increase the relevance of economic learning and students' skills in creative and collaborative thinking. As an implication of the research